FAKTOR-FAKTOR YANG MEMPENGARUHI STABILITAS EKONOMI SERTA IMBASNYA TERHADAP KINERJA SEKTOR KEUANGAN DI INDONESIA (PENDEKATAN COINTEGRATION, ERROR CORRECTION MODEL DAN FINANCIAL DEEPENING) - Muhammad R Assel (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2019)
The research and study cover a theoretical discussion and empirical study on factors affecting the Economic stability and their impact on the performance of the financial sector based on Quartely data from 2001Q1 to 2017Q2. The research employs the Cointegration and Engle Granger-Error Correction Model (ECM) approach by applying the Ordinary Least Square (OLS) method. The ECM is performed to anticipate the possibility of errors and disparity between the theoretical model and the statistical model as well as to identify long-term balance and validity of the model employed in the research. The research results indicate that within a long-term period, there is balance between changes in the GDP and the monetary variables i.e. interest rate, inflation, M2 and rupiah exchange rate despite the fact that the M2 variable does not significantly affect the GDP within the observed period. On the other hand, within a short-term period changes in the GDP affected significantly by the ECT variable. Within such a period, interest rate, inflation, M2 and exchange rate variables do not significantly affect GDP. Thus, it can be concluded that the GDP tend to respond to changes occurring in monetary variables, especially interest rate, inflation and M2. Currently, the result of financial performance analysis shows that the average of the financial deepening quartely in Indonesia during the observation period is 3.80 percent. In addition, the quartely average of Indonesia's economic growth was 1.36 percent, while M2 growth during the same period was 3.03 percent.